Student needs in digital persuasive writing: Integration of literacy, rhetoric, and reflective awareness - Nurfidah Nurfidah; Vismaia S. Damaianti; Dadang S. Anshori; Khaerudin Kurniawan (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2026)
This research examines how students learn to produce digital persuasive writing across social, business, and theoretical areas, emphasizing skills in digital literacy and rhetorical competence and reflexivity regarding social and business fields. The findings indicate a mismatch between what students are currently able to do and what they will require in academic and professional settings. Drawing on both quantitative and qualitative data collected using questionnaires, interviews, classroom observations, and documents of Akademi Bisnis Lombok’s digital business program students, this research utilizes a mixed-methods approach. The findings of this study show that many students have difficulty with forming coherent arguments, using rhetorical strategies (ethos, pathos, and logos), and making use of visual components in digital media. These issues demonstrate an incapacity to transfer rhetorical skills to authentic situations. The study identifies this and stresses the importance of project-based learning including collaborative and reflective work within digital and digital-based media in advancing adaptive, critical, and context-specific communication skills within digital and digital-based contexts.